Derivational Potential of Pronouns in German and Russian languages - A. V. Melgunova (Научный диалог)
The question of the use of pronouns as an element in the process of word formation of lexical units of the German and Russian languages is considered. The material was texts related to different genres: journalistic, popular science, scientific, artistic. The novelty of the research is seen in the comparison of the word-formation potential of pronouns in two languages, the word-formation system of which has some differences. The result of a comparative analysis of vocabulary related to different parts of speech is presented. Particular attention is paid to the possibility of using personal pronouns that are involved in nominal word formation. It is shown that lexical units with components — personal pronouns in the Russian language are less typical, however, they are used in texts of a certain subject and in some cases are tracing copies from the corresponding foreign words. Attention is paid to the emergence of neologisms and occasionalisms, the use of borrowings. The question is raised about the role of context in the interpretation of words with pronominal components. It is concluded that the derivational potential of pronouns is higher in German, but the lexical units of the Russian language can also be formed using similar elements. An increase in the number of words of this type in the Russian language is noted due to the translated terminology from the Germanic languages.